Financial Credit in Agricultural Development in Côte D’ivoire - Celestin, N’GORAN Koffi (Journal of Agricultural Studies, 2021)
Agriculture has long been Côte d’Ivoire’s main source of export income and the first largest sector providing employment. For several decades, Ivorian agriculture remained unmodernized. The modernization of agriculture requires both public and private funding. Despite some efforts, financing of agriculture is not effective in Côte d’Ivoire due to the lack of real commitment from the private sector and commercial banks. The results showed that in the long-term agricultural credit and other variables have a positive and significant influence on agricultural added value. It is therefore recommended to increase agricultural credit and extend it to small producers.